Separate determination of thickness and optical parameters by surface plasmon resonance: accuracy consideration - Rengevych, O.V.; Shirshov, Yu.M.; Ushenin, Yu.V; Beketov, A.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Reliability and precision of characterization of surface layers by SPR method was evaluated with relation to the experimental conditions and the strategy of extracting the film parameters. Consideration is bound up with sensor applications of SPR phenomenon and focused at problems of separate extraction of optical constants and thickness of the layer and determination of the total quantity of material constituting the surface coverage. Computational scheme for modeling the SPR resonance for multilayer assembly, based on the Abeles matrix formalism, is presented. It is demonstrated that improper choice of the angle range the measurements are taken over may result in ambiguity in determination of the real part of the refractive index n and the film thickness d. Nevertheless, the total quantity of material in the film can be estimated with reasonable accuracy even when correct separate extraction of n and d parameters is hampered by experimental errors and inadequacy of theoretical model of layered system.